Painful procedures and pain management in newborns admitted to an intensive care unit - Vanderlei Amadeu da Rocha; Isília Aparecida Silva; Sanseray da Silveira Cruz-Machado; Mariana Bueno
ABSTRACT Objective: To characterize painful procedures, analgesic strategies, vital signs, and pain scores in hospitalized newborns. Method: This is a primary, observational, prospective clinical study, developed in a Brazilian public hospital. Demographic data, painful procedures, pain relief measures, vital signs, and pain scores were collected from the clinical records of 90 newborns admitted to the intensive care unit and evaluated between admission and the third day of admission. For statistical analysis, the software Statistic Package for the Social Sciences and the R Software were used. Results: Newborns underwent 2,732 painful procedures, 540 non-pharmacological and 216 pharmacological strategies. The most frequently performed procedure was the heel prick (20.96%). The most commonly recorded non-pharmacological strategy was dim lighting (28.33%) and continuous fentanyl (48.83%) was the main pharmacological measure adopted. Pain score and vital signs show variability in the period evaluated. Conclusion: Despite the high number of painful procedures, pain assessment records do not reflect procedural pain and the use of analgesic strategies was insufficient.